Hubungan Self Efficacy dan Kemandirian Belajar Terhadap Hasil Belajar Siswa Pada Materi Sel - Shinta Aulia Rachman; Romy Faisal Mustofa; Dea Diella (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
This study aims to determine the correlation between self-efficacy and learning independence on student learning outcomes in cell material in XI Math and Science class of 6 Senior High School Tasikmalaya in the 2021/2022 academic year. The method in this study uses the correlational method. The population this research of class XI MIPA SMAN 6 Tasikmalaya in the 2021/2022 academic year. The sample used was class XI MIPA 5 and XI MIPA 7 for the academic year 2021/2022 with a total of 72 students, the sample was taken using purposive sampling technique. Data collection techniques used tests in the form of daily tests of cell material and non-tests in the form of instruments self-efficacy questionnaires and learning independence questionnaires. Hypothesis testing using multivariate correlation test. The results of the correlation test analysis show that the relationship between self-efficacy and learning independence on student learning outcomes is obtained by a correlation coefficient (R) of 0.489, which means that the strength of the relationship between variables is at a moderate level, and the coefficient of determination (R2) is 0.239, which means that the variables of self-efficacy and learning independence are variable. collectively contributed 23.9% to student learning outcomes